2015
DOI: 10.1002/app.42682
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental studies for gas assisted extrusion forming of molten polypropylene

Abstract: In this study, the experiments of gas-assisted extrusion (GAE) for molten polypropylene were carried out under different gas pressures, the different extrudate deformations and sharkskin defects of melt were observed. To ascertain the effects of gas on melt extrusion, non-isothermal numerical simulation of GAE based on gas/melt two-phase fluid model was proposed and studied. In the simulations, the melt extruded profile, physical field distributions (velocities, pressure drop, and first normal stress differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The relationship between shear rate and volume flow rate is shown in Figure 8. It can be seen that the volume flow rate increases with the increase of shear rate, and the increasing trend gradually slows down, which verifies the correctness of the proposed viewpoint, a the viewpoint is consistent with the extrusion molding of PP micro tubes [20]. shown in Table 2.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The relationship between shear rate and volume flow rate is shown in Figure 8. It can be seen that the volume flow rate increases with the increase of shear rate, and the increasing trend gradually slows down, which verifies the correctness of the proposed viewpoint, a the viewpoint is consistent with the extrusion molding of PP micro tubes [20]. shown in Table 2.…”
Section: Resultssupporting
confidence: 78%
“…The relationship between shear rate and volume flow rate is shown in Figure 8. It can be seen that the volume flow rate increases with the increase of shear rate, and the increasing trend gradually slows down, which verifies the correctness of the proposed viewpoint, a the viewpoint is consistent with the extrusion molding of PP micro tubes [20]. It is assumed that the gap between the die and the mandrel is equal at the extrusion die forming section, and the melt flow is balanced so each point on any concentric circle of the cavity cross section has the same velocity field and stress field.…”
Section: Resultssupporting
confidence: 74%
“…Liang [ 24 ] introduced nitrogen into the HDPE melt round bar and die through the slit to form a stable gas cushion, which effectively reduced the die pressure drop and extrusion expansion rate of the melt and improved the quality and yield. Ren [ 25 , 26 , 27 ] found that the gas-assisted technology can overcome extrusion expansion, improve the surface quality of the micro-tube, and reduce the pressure, shear stress, and first normal stress difference of the melt inside the die through experimental research and numerical analysis. Liu [ 28 ] analyzed the effect of the inner gas cushion layer pressure on the melt pressure difference and the size of the micro-tube by numerical simulation and determined the control steps to stabilize the gas cushion layer during gas-assisted extrusion through experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Huang [13] and Liu et al [14] studied the formation and stability of gas layer film during GAE by means of experiments and simulations, and it was proved that the use of gas-assisted method can effectively eliminate some bad phenomena, such as extrusion expansion, pressure drop during extrusion, and the interface instability. For decades, many investigations in this filed, both experiments and simulations, [15][16][17][18][19][20][21][22][23][24][25][26][27] have shown the prospect and superiority of GAE technology, and many scholars [28][29][30][31][32][33][34][35][36][37] have demonstrated that GAE promotes the melt slippage phenomenon.…”
Section: Introductionmentioning
confidence: 99%